TRIM65 supports bladder urothelial carcinoma cell aggressiveness by promoting ANXA2 ubiquitination and degradation. (28th October 2018) - Wei, Wen-Su; Chen, Xin; Guo, Li-Yi; Li, Xiang-Dong; Deng, Ming-Hui; Yuan, Gang- Jun; He, Le-Ye; Li, Yong-Hong; Zhang, Zhi-Lin; Jiang, Li-Juan; Chen, Ri-Xin; Ma, Xiao-Dan; et al.
Abstract: Clinically, most of human urothelial carcinoma of the bladder (UCB)-related deaths result from tumor metastasis, but the underlying molecular mechanisms are largely unknown. Recently, a growing number of tripartite motif (TRIM) family members have been suggested to be important regulators for tumorigenesis. However, the impact of most TRIM members on UCB pathogenesis is unclear. In this study, TRIM65 was first screened as an important oncogenic factor of UCB from the Cancer Genome Atlas (TCGA) database and was validated by a large cohort of clinical UCB tissues. By in vitro and in vivo experiments, we demonstrated that TRIM65 promotes UCB cell invasive and metastatic capacities. Notably, we showed that TRIM65 modulates cytoskeleton rearrangement and induces UCB cells epithelial-mesenchymal transition by the ubiquitination of ANXA2, ultimately leading to an enhanced invasiveness of UCB cells. Importantly, UCBs with high expression of TRIM65 and low expression of ANXA2 showed the poorest outcome. Collectively, our results suggest that the overexpression of TRIM65 has an essential oncogenic role via ubiquitination of ANXA2 in UCB pathogenesis, and that such could be used as a novel prognostic marker and/or therapeutic target for UCB. Highlights: TRIM65 is overexpressed in UCBs and is an independent prognostic biomarker. TRIM65 promotes UCB cell invasive and metastatic capacities. TRIM65 modulates cytoskeleton rearrangement and induces UCB cell EMT. TRIM65 promotes ANXA2 ubiquitination and degradation in UCB cells. ANXA2 is responsible for TRIM65-induced UCB cell EMT, morphological alteration and invasiveness.